Impact of the COVID pandemic on mental health and training opportunities of Public Health Residents from 4 European countries: A cross-sectional study - Failla, Giovanna; Caminiti, Marta; Chen-Xu, José; Lo Moro, Giuseppina; Berselli, Nausicaa; Cabral Ferreira, Madalena; Malcata, Filipa; Peyre-Costa, David; Croci, Roberto; Soldà, Giorgia; Capodici, Angelo; Morcavallo, Caterina; et al. (Frontiers in Public Health, 2023)
Objectives There is little evidence on the impact of the COVID-19 pandemic on Public Health Residents' (PHR) mental health (MH). This study aims at assessing prevalence and risk factors for depression, anxiety and stress in European PHR during the COVID-19 pandemic. Methods Between March and April 2021, an online survey was administered to PHR from France, Italy, Portugal and Spain. The survey assessed COVID-19 related changes in working conditions, training opportunities and evaluated MH outcomes using the Depression Anxiety Stress Scales-21. Multivariable logistic regressions were applied to identify risk factors. Results Among the 443 respondents, many showed symptoms of depression (60.5%), anxiety (43.1%) and stress (61.2%). The main outcome predictors were: female gender for depression (adjOR = 1.59, 95%CI [1.05–2.42]), anxiety (adjOR = 2.03, 95%CI [1.33–3.08]), and stress (adjOR = 2.35, 95%CI [1.53–3.61]); loss of research opportunities for anxiety (adjOR = 1.94, 95%CI [1.28–2.93]) and stress (adjOR = 1.98, 95%CI [1.26–3.11]); and COVID-19 impact on training (adjOR = 1.78, 95%CI [1.12–2.80]) for depression. Conclusions The pandemic had a significant impact on PHR in terms of depression, anxiety and stress, especially for women and who lost work-related opportunities. Training programs should offer PHR appropriate MH support and training opportunities.